Preliminary sceening of indigenous collections of turmeric against shoot borer (Conogethes punctiferalis Guen.) and scale insect (Aspidiella hartii Sign.) - Liji, K C Velayudhan, R S (Journal of Spices and Aromatic Crops, 2003)
The incidence of shoot borer (Conogethes punctiferalis Guen.) and scale insect (Aspidiella hartii Sign.) was scored subjectively on 0-9 scale in an indigenous collection of 489 accessions under field epiphytotic conditions at Vellanikkara, Thrissur during 2001 cropping season. The collections belonged to 21 morphotypic groups of turmeric from different agroclimatic conditions in India. Morphotypic group wise incidence of shoot borer indicated that the lowest incidence of mean score 2 was observed in morphotype 2 followed by 2.6 in morphotype 14. Lowest scale insect incidence of 0.5 was scored in morphotype 6. Eighty accessions were free of scale insect but were susceptible to shoot borer. Maximum susceptibility to the scale insect was noticed in the case of IC 137023 and IC 88895. A total of 22 accessions were tolerant to shoot borer with <3 score.